Investigating the Sources of Formaldehyde and Corresponding Photochemical Indications at a Suburb Site in Shanghai From MAX‐DOAS Measurements. Issue 6 (18th March 2021) - Zhang, Sanbao; Wang, Shanshan; Zhang, Ruifeng; Guo, Yanlin; Yan, Yuhao; Ding, Zhenfeng; Zhou, Bin
Abstract: Multi‐AXis‐Differential Optical Absorption Spectroscopy (MAX‐DOAS) measurements were performed to obtain vertical distributions of nitrogen dioxide (NO2 ), formaldehyde (HCHO) and glyoxal (CHOCHO) from October 17 to November 21, 2019 in Qingpu, a suburb of Shanghai, China. The consistencies of MAX‐DOAS and other independent observations of HCHO and NO2 verified the effectiveness of the inversion results. The secondary formation was identified as the predominant HCHO sources (57.4% of all) by a statistical regression analysis of HCHO with carbon monoxide (CO) and CHOCHO. The photochemical indications of HCHO were investigated through the ratios of HCHO to CHOCHO ( R GF ) and NO2 ( R FN ). The results showed that anthropogenic influence on R GF mainly existed in the layer of 0–800 m. The dependences of anthropogenic emission on R GF were negative in 0–200 m layer and positive in 200–800 m layer when NO2 level was higher than 5 ppbv. The sensitivity analysis of O3 formation in 0–2 km layer was concluded as follows: between 9:00 and 11:00 LT, the O3 formation was controlled by VOC‐limited regime alone; while it turned into transition regime in 1.7–2 km layer from 11:00 to 13:00 LT; then the transition regime moved down to the layer of 1.3–1.4 km from 13:00 to 15:00 LT and the NOx ‐limited regime began to occur in 1.4–2.0 km layer. Key Points: Separate the different HCHO sources by a more suitable tracer pair of CO‐CHOCHO The anthropogenic influence on R GF presented different characteristics with height The limited regime of O3 formation can convert with height